Analyse The Factor Influencing Relapsing Level at Patient Stroke in Space of Poly Nerve Gambiran Regional Hospital of Town Kediri - solehah, eka; Novita Ana Anggraini (Universitas STRADA Indonesia, 2016)
Relapsing Stroke in causing several factors among other things pattern of eating, being less athletic and patterned thinking which is not controlled, resulting in increased blood pressure, and oxygen supply in the brain is not maximal, and generates the impact of like sluggishness, communications trouble, and awareness degradation. This research target is knowing the pattern influence of eating, stress, compliance of athletic regimen therapy and activity to the occurrence of relapse level at patient of stroke of space of poly of nerve of RSUD Gambiran of Town Kediri. This research design is analytic of correlational with the approach of cross sectional. Population as many as 280 people, and sample as many as 30 respondents taken by technique is purposive sampling. The instrument used represents the questionnaire as many 58 consisting of the eating pattern, stress, compliance of therapeutic regimen, and athletic activity. This research on March, 2015. Results of analysis show there is pattern influence eating the p-value = 0.001, there is no influence of stress p-value = 0.214, compliance of therapeutic regimen p-value = 0.936 and athletic activity of p-value = 0.368 to relapse level in patients stroke in space of poly of nerve of RSUD Gambiran of Town Kediri. Pattern eating to influence the cardiovascular condition till cause the attack of stroke. Relapsing Stroke influenced by eating under the way food, because that matter is more dominant for relapsing stroke, suggested by the respondent of a lot of searching information and motivating one of them is by applying routine control and healthy eating patterns.